Assessment of Youth Empowerment and Social Support Operation in Context Education - Charles, Osu uchechukwu; Olalekan, Imran Mutiu; Ajiye, Olakunle Titus (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Youth empowerment stands as a crucial approach for fostering sustainable development in context education, particularly in countries such as Nigeria where the youth population is significant. This study examines the implementation and outcomes of the Youth Employment and Social Support Operation (YESSO) initiative in Oyo State, Nigeria. YESSO aims to combat poverty and unemployment among young people by facilitating access to job opportunities and social assistance. Employing a descriptive survey methodology, data were gathered from 180 program beneficiaries and stakeholders. The findings indicate a substantial positive impact of YESSO on the lives of participants. The program has effectively delivered essential services and skills training, fostering asset acquisition and enhancing the financial capacity of unemployed youth and impoverished households. Additionally, YESSO has contributed positively to the health and educational prospects of beneficiaries. Nonetheless, challenges persist, including payment delays, insufficient tools for work, and mismanagement of grants. The study emphasizes the crucial role of youth empowerment initiatives in addressing unemployment and poverty and also identifies opportunities to improve program implementation and sustainability in context-based education. Furthermore, recommendations put forward include enhancing public awareness of the program, ensuring prompt fund disbursement, and addressing logistical hurdles to optimize the effectiveness of YESSO.